Legal Protection of Traditional Cultural Expressions in Aceh: A Comparative Legal Analysis of Islamic Law and Positive Law in Indonesia - Nasrianti, Nasrianti; Sanusi, Sanusi; Azhari, Azhari; Ilyas, Ilyas (AL-ISTINBATH : Jurnal Hukum Islam, 2025)
This study aims to analyze the legal protection of traditional cultural expressions (TCEs) in Aceh through a comparative legal analysis of Islamic law and Indonesian copyright law. While TCEs play a crucial role in preserving cultural heritage, their legal protection remains insufficient due to regulatory inconsistencies and enforcement challenges. This research method used is normative juridical research. The primary data sources in this study include Law No. 28 of 2014 on Copyright, Law No. 11 of 2006 on Aceh Governance, and relevant Qanun in Aceh that govern the protection of cultural heritage and intellectual property. The data analysis was conducted through a comparative evaluation of Islamic law perspectives and positive law in Indonesia. The results of this study indicated that Indonesia's legal framework provides formal recognition of TCEs, yet lacks a robust enforcement mechanism. In contrast, Islamic law views TCEs as intellectual property that must be safeguarded under the principles of hifdz al-mal (protection of property) and maslahah mursalah (public welfare). Harmonizing these two legal perspectives is essential to establish a comprehensive and culturally sensitive legal framework. This study contributes to the discourse on intellectual property rights by integrating Islamic and Indonesian legal perspectives, offering a pathway for more effective legal protection of TCEs in Aceh.